1995
DOI: 10.1139/v95-078
|View full text |Cite
|
Sign up to set email alerts
|

A solid-state 13C NMR and theoretical investigation of carbonyl and thiocarbonyl carbon chemical shift tensors

Abstract: The carbon chemical shift tensors of the carbonyl and thiocarbonyl groups of acetamide, thioacetamide, thioacetanilide, 4'-methoxyacetanilide, and 4'-methoxythioacetanilide have been experimentally determined using dipolar -chemical shift solid-state 13c NMR spectroscopy. The magnitudes of the three principal components of the carbon chemical shift tensors are found to exhibit marked variations between the carbonyl and thiocarbonyl functionalities. However, in contrast to the conclusions of an earlier comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 30 publications
7
27
0
Order By: Relevance
“…The experimental 13 The principal values given in Table 1 correlate qualitatively with the principal values measured by Kirby et al [8] for the trigonal carbon atoms in acetamide, acetanilide, 4 0 -methoxyacetanilide, and the corresponding thiocarbonyl derivatives. These authors found that each of the three principal values for the carbonyl carbon atoms reveals a significant sensitivity to a substitution of the carbonyl oxygen with sulfur.…”
Section: Experimental Nmr Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…The experimental 13 The principal values given in Table 1 correlate qualitatively with the principal values measured by Kirby et al [8] for the trigonal carbon atoms in acetamide, acetanilide, 4 0 -methoxyacetanilide, and the corresponding thiocarbonyl derivatives. These authors found that each of the three principal values for the carbonyl carbon atoms reveals a significant sensitivity to a substitution of the carbonyl oxygen with sulfur.…”
Section: Experimental Nmr Resultssupporting
confidence: 79%
“…The principal values and tensor orientation data obtained for EC, ETTC, DPC, ETTC, and DMTTC in this study complement the previous data on the ionic potassium carbonates and thiocarbonates [1], the PAHs [7,[32][33][34][35][36][37], and the C/TC compounds studied by Kirby et al [8]. Figure 5 compares the bonding structure of the planar carbonate and thiocarbonate groups in the neutral dialkyl compounds with the bonding structure of the planar groups in the monoalkyl carbonate and thiocarbonate anions.…”
Section: Chemical Shift Tensor Orientationssupporting
confidence: 81%
See 2 more Smart Citations
“…IGAIM calculations yield the three principle components, which are averaged to obtain the isotropic shifts. Ideally, the IGAIM principle components should be compared with the experimental values if they are available (15,16 For personal use only. Table 4 is seen that in going from 5 to 6 the chemical shifts of the terminal carbons and the central carbon atom increase by 10.5 and 15.2 ppm, even though the electron populations of terminal carbons C 1 and C3 and the center carbon C2 increase by 0.067 and 0.101, respectively (Fig.…”
Section: Calculations On Hydrocarbonsmentioning
confidence: 99%